HIMPUNAN SEMI BUKA DALAM RUANG TOPOLOGI - Djuwandi, Djuwandi (MATEMATIKA, 2010)
For study this paper we required about topological space, in particular the topology on the real numbers, while for assessing semi-open set are expected to know about an open set, closed set, closure (closure) set, interior sets, etc.